2017
DOI: 10.1016/j.cub.2017.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Epithelia: Understanding the Cell Biology of Intestinal Barrier Dysfunction

Abstract: Barrier dysfunction in the intestine is a common characteristic of aging organisms. A recent study provides new insight into the cell biology of this phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…Aging is characterized by progressive health decline leading to mortality, yet the underlying pathophysiology remains elusive. There is an emerging understanding that maintaining intestinal barrier function during aging is critical to organismal health and longevity ( Cesar Machado and da Silva, 2016 , Choi et al., 2017 , Clark et al., 2015 , Clark and Walker, 2018 , Hu and Jasper, 2017 , Rera et al., 2013 , Rera et al., 2012 , Thevaranjan et al., 2017 ). At the same time, an age-related remodeling of epithelial junctions has been implicated in loss of barrier function in aged animals ( Clark et al., 2015 , Meier and Sturm, 2009 , Ren et al., 2014 , Resnik-Docampo et al., 2017 , Tran and Greenwood-Van Meerveld, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aging is characterized by progressive health decline leading to mortality, yet the underlying pathophysiology remains elusive. There is an emerging understanding that maintaining intestinal barrier function during aging is critical to organismal health and longevity ( Cesar Machado and da Silva, 2016 , Choi et al., 2017 , Clark et al., 2015 , Clark and Walker, 2018 , Hu and Jasper, 2017 , Rera et al., 2013 , Rera et al., 2012 , Thevaranjan et al., 2017 ). At the same time, an age-related remodeling of epithelial junctions has been implicated in loss of barrier function in aged animals ( Clark et al., 2015 , Meier and Sturm, 2009 , Ren et al., 2014 , Resnik-Docampo et al., 2017 , Tran and Greenwood-Van Meerveld, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal epithelium acts as a selectively permeable barrier that permits the absorption of nutrients, ions, and water, while maintaining an effective defense against intraluminal toxins, antigens, and enteric microorganisms. In recent years, studies in diverse organisms, including worms ( Dambroise et al., 2016 , Gelino et al., 2016 ), flies ( Dambroise et al., 2016 , Rera et al., 2011 , Rera et al., 2012 ), fish ( Dambroise et al., 2016 ), rodents ( Thevaranjan et al., 2017 ), and primates ( Mitchell et al., 2017 , Tran and Greenwood-Van Meerveld, 2013 ), have shown that intestinal barrier dysfunction is a pathophysiological hallmark of aging ( Hu and Jasper, 2017 ). Loss of intestinal barrier function, in aged flies, is linked to organismal health decline, including loss of motor activity, systemic metabolic defects, and impending mortality ( Clark et al., 2015 , Rera et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with their extended lifespan, old per 01 mutants showed a lower percentage of "smurfs" relative to controls, indicating a delay in aging-related intestinal barrier dysfunction (Fig. 6a) NATURE COMMUNICATIONS | https://doi.org/10.1038/s41467-020-15617-x ARTICLE As aging-related intestinal barrier dysfunction is linked to overproliferation and tissue dysplasia in the gut 38 , we next tested if loss of per or intestinal UCP4C overexpression delayed agingrelated cellular proliferation in the gut. Per protein has previously been shown to regulate ISC regeneration during acute intestinal stress 39 .…”
Section: Per and Ucp4c Control Intestinal Homeostasis Via Ros Levelsmentioning
confidence: 83%
“…However, the maintenance of gut homeostasis can be compromised in certain cases. For example, during aging, there is an overall decline in tissue homeostasis maintenance with the presence of numerous immature or misdifferentiated cells (Jasper, 2015;Hu and Jasper, 2017). Another case where homeostasis can also be disrupted is upon exposure to xenobiotic or pathogens (such as opportunistic bacteria) that damage or kill cells impairing their functions (Bonfini et al, 2016).…”
mentioning
confidence: 99%